2009 IEEE International Conference on Communications Workshops 2009
DOI: 10.1109/iccw.2009.5208000
|View full text |Cite
|
Sign up to set email alerts
|

Business Impact of Relay Deployment for Coverage Extension in 3GPP LTE-Advanced

Abstract: Relays are expected to be a cost efficient way to fulfill requirements on high data rate coverage in next generation cellular networks, like LTE-Advanced. This paper presents a cost model and the respective analysis used for investigating the impact of relaying on cost savings for operators. The approach consists of defining the service level that next generation cellular networks should provide and deriving deployments of eNBs and RNs (or equivalently isoperformance scenarios) that fulfill these requirements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…A basic trace file may contain event entries, detailed packet information from wired or wireless channel and routing information. Various trace file formats are explained in [28]. Simulation results shown later in this document are mostly gathered from the trace files but occasionally separate runtime logging is needed in order to obtain desired information.…”
Section: Network Simulatormentioning
confidence: 99%
“…A basic trace file may contain event entries, detailed packet information from wired or wireless channel and routing information. Various trace file formats are explained in [28]. Simulation results shown later in this document are mostly gathered from the trace files but occasionally separate runtime logging is needed in order to obtain desired information.…”
Section: Network Simulatormentioning
confidence: 99%
“…Deployment of RNs brings many benefits such as coverage, capacity and cell edge throughput enhancements to the LTE-Advanced network [208,209]. At the expense of deployment cost [210,211], achievable gains in relaying networks substantially depend on the location and number of deployed relay nodes. In [212], three scenarios were proposed based on the number of relays per cell (RPC), and network performance was evaluated using Monte-Carlo simulation.…”
Section: Technical Aspectsmentioning
confidence: 99%
“…Furthermore, RNs do not have strict installation guidelines with respect to radiation, visual disturbance, and planning regulation. Therefore, relaying is regarded a cost-efficient technology [1]. Previous technical studies have further shown that RNs promise to increase the network capacity and to better distribute resources in the cell, or extend the cell coverage area [2,3].…”
Section: Introductionmentioning
confidence: 99%